1987
DOI: 10.1111/j.1365-3083.1987.tb02307.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific Deposition of Serum Amyloid A Protein 2 in the Mouse

Abstract: The homogenates of amyloid-laden spleens prepared from CBA mice were analysed by SDS-PAGE and immunoblotting employing rat anti-murine monoclonal antibody, MSA 4-26. The results showed that the precursor of amyloid A protein (AA), serum amyloid A protein 2 (SAA2), and SAA intermediates with molecular weights of 10,000, 9000, and 8000 were contained in amyloid-laden tissues. The experiment using sonicated spleen cells and acute phase murine sera showed a delay in the degradation rate of SAA2 on cell fragments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 22 publications
3
45
1
Order By: Relevance
“…SAA proteins are acute-phase reactants that originate in the liver and are liberated into the plasma after cytokine stimulation Vogel and Sipe, 1982). In the mouse, the two acute-phase SAA proteins are SAA1.1 and SAA2.1; during inflammation-associated amyloid formation, only the SAA1.1 isoform is deposited into amyloid (Meek et al, 1986;Shiroo et al 1987). The CE/J mouse contains a single SAA gene, SAA2.2, which seems to be a composite of the SAA1.1 and SAA2.1 genes .…”
mentioning
confidence: 99%
“…SAA proteins are acute-phase reactants that originate in the liver and are liberated into the plasma after cytokine stimulation Vogel and Sipe, 1982). In the mouse, the two acute-phase SAA proteins are SAA1.1 and SAA2.1; during inflammation-associated amyloid formation, only the SAA1.1 isoform is deposited into amyloid (Meek et al, 1986;Shiroo et al 1987). The CE/J mouse contains a single SAA gene, SAA2.2, which seems to be a composite of the SAA1.1 and SAA2.1 genes .…”
mentioning
confidence: 99%
“…The function of the different isoforms is not clear, and in humans it has been reported that there is no disease-specific pattern of SAA isoforms in dis- eases including amyloidosis. On the other hand, only SAA 2 , which is one of the isoforms , seems to be the precursor of AA in the mouse [15]. Alsemgeest [1] reported that bovine SAA has some specific isoform expression patterns, and the sera obtained from cows with different diseases showed variable ratios of the isoforms, and furthermore, only one isoform was detectable in the serum of a cow suffering from spontaneous AA-amyloidosis.…”
mentioning
confidence: 99%
“…The disease is characterized by the deposition of amyloid fibrils, which are derived from A-SAA [11], in the major organs of the body. It has been demonstrated in mouse that the amyloid fibrils are principally derived from the A-SAA2 isoform [22,24]. Given that amyloidosis depends on high circulating levels of a single pathogenic protein, A-SAA2, a reduction in its concentration could form the basis of a therapeutic model.…”
Section: Resultsmentioning
confidence: 99%
“…The mouse is a useful experimental model for both secondary amyloidosis [22] and atherosclerosis. The mouse SAA gene family comprises three A-SAA genes (Saa1, Saa2 and Saa3), a constitutively expressed gene (Saa5 ) and a pseudogene (Saa4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation